Physical and chemical properties of some 4-amino-5-(furan-2-, 2-metylfuran-3-yl)-1,2,4-triazole-3-thiol alkyl derivatives - D. M. Danilchenko; V. V. Parchenko; O. I. Panasenko; Ye. G. Knysh (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Publications of domestic and foreign scientists in the last ten years clearly show that the search for new molecules among 1,2,4-triazole furan derivatives has not only theoretical interest in the study of physical and chemical properties of compounds, but also has a practical significance on the implementation of the most active agents in various spheres of human activity. The most striking example is the registration of new domestic veterinary drug «Tryfuzol 1% solution for injections» (registration certificate AB-05486-01-14 from 01.10.2014). Active substance of the «Tryfuzol» is a water-soluble substance, which is furan derivative of 1,2,4-triazole-3-thione according to the chemical formula.